Análise dos atendimentos do SAMU 192: Componente móvel da rede de atenção às urgências e emergências - Almeida, Priscila Masquetto Vieira De (2016)
ABSTRACTObjective: To analyze the services provided by SAMU 192: the mobile component of the Urgency and Emergency Care Network, in the city of Botucatu, SP, Brazil.Methods: An exploratory-descriptive field study of a time series with a quantitative approach was performed. This study focused on the analysis of care provided by SAMU 192, between August 2011 and January 2012, based on 2635 service files.Results: There was a predominance of clinical occurrences and seizure as the main complaint (12.16%). The majority of victims (96.08%) were conscious upon arrival of the SAMU 192 team. The city's central region was the one that showed the greatest demand for care (25.83%). The main outcome of occurrences was the referral of victims to a hospital (81.61%).Conclusion: The present study showed the importance of SAMU 192 in the Urgency and Emergency Care Network. A high number of occurrences and the associations between several complaints and age, sex and place of occurrence stood out in this study.